Predictors and Timing to Viral Suppression in HIV-Infected Pregnant Women in the University of Zimbabwe Birth Cohort Study During the Era of Lifelong Antiretroviral Therapy (Option B+ Treatment Strategy) - Duri, Kerina; Munjoma, Privilege Tendai; Mazhandu, Arthur John; Marere, Tarisai; Gomo, Exnevia; Banhwa, Simeon; Jordi, Sebastian Bruno Ulrich; Misselwitz, Benjamin; Mazengera, Lovemore Ronald (Frontiers in Virology, 2022)
Background Achieving and maintaining viral suppression (VS) in people living with HIV/AIDS on antiretroviral therapy (ART) remains a crucial clinical goal, more so in pregnancy to prevent mother-to-child-transmission (MTCT). There is need to understand VS kinetics and barriers to achieving it, in order to meet the target of eliminating HIV-MTCT by 2030. Methods HIV-infected pregnant women ≥20 weeks of gestation with different durations of Tenofovir/Lamivudine/Efavirenz exposures seeking antenatal care services at four primary health centres in high-density residential areas in Harare, Zimbabwe were enrolled in the University-of-Zimbabwe-Birth-Cohort-Study. Plasma viral load (VL) was quantified by reverse-transcriptase-polymerase-chain-reaction. Demographic, clinical, socio-economic, HIV-and ART-related-factors were tested in multivariable logistic regression analyses as potential predictors for VS and undetectable-VL. Results From March 2016 to June 2019, 608 HIV-infected pregnant women were enrolled. 63 (10.4%) were self–reported-ART-naïve; 324 (53.3%) and 221 (36.3%) initiated ART pre-and post-conception, respectively. Time from ART-initiation to VS (VL≤1000 copies/mL) in 95% of women was 126 days. Overall lack of VS (VL>1000 copies/mL) was observed in 133 (21.9%) women being 76.2%, 27.4% and 7.7% in self–reported-ART-naïve, post-conception and pre-conception groups, respectively. Undetectable-VL (≤50 copies/mL) was observed in 371 (61.2%), and low-level-viremia (51-1000 copies/mL) in 102 (16.8%) women. In multivariable models for all participants regardless of ART-exposure, being on ART was the strongest predictor for both VS and undetectable-VL (odds ratio 95% confidence interval, OR (CI):8.9(4.2-19.5) and 8.1(3.2-24.4), respectively). For women on ART, duration of ART use >126 days was the strongest predictor with OR (CI):6.7 (3.3-14.0) for VS and 8.5(5.6-13.1) for undetectable-VL. Other relevant predictors for favourable virological outcomes were older maternal age, HIV-status disclosure, absence of ART-side effects and self-reported depression. Having a spouse/intimate-partner on ART predicted a 4-times higher likelihood for VS. Discussion Lack of VS was frequently observed in this Harare cohort of pregnant women, mainly due to new HIV diagnosis, hence not being on ART and suboptimal duration of ART-exposure. Since VS for 95% of women needed about 4-months of ART-exposure, eliminating HIV-MTCT will require timely screening and commencing women together with their spouses/intimate-partners on ART before pregnancy or early after conception. www.clinicaltrials.gov,trial registration number: NCT04087239.